Hybrid Biopellets Characterization of Gamal Wood (Gliricidia sepium) and Robusta Coffee Husk at Various Compositions - Putri, Mangifera Indica Dhaifullah Wangun; Murda, Rio Ardiansyah; Maulana, Sena; Octaviani, Eti Artiningsih; Sari, Nurika Arum; Hasibuan, Mhd Muhajir; Aulia, Fauzan; Hidayat, Wahyu (Jurnal Sylva Lestari, 2024)
Biopellets from gamal wood (Gliricidia sepium) as a biomass energy resource could be an alternative to replace fossil fuels due to having met standards based on moisture content, ash content, fixed carbon, calorific value, and density. Unfortunately, they still had high levels of volatile matter. Robusta coffee husk was a material with high nitrogen content, which is suspected of being able to bind aromatic substances in volatile organic compounds. This study aims to evaluate the quality of biopellets and determine the optimum composition of the biopellets from gamal wood and coffee husk. The blended composition of gamal wood and coffee husk biopellets studied were 100:0, 75:25, 50:50, 25:75, and 0:100. The biopellets were manufactured using the material size of 40-60 mesh with a pressure of 173.51 MPa. The best biopellet was produced in the composition of 75% gamal wood and 25% coffee husk, with a density of 0.85 g/cm3, moisture content of 8.03%, ash content of 3.92%, volatile substances of 78.01%, fixed carbon of 18.07%, and calorific value of 4,176 cal/g. The biopellet quality met the standards of SNI 8021:2014 and EN 14061-2, except for ash content. Adding coffee husk reduced gamal wood biopellet’s volatile matter, increasing the fixed carbon and density of gamal wood biopellets. Keywords: alkali immersion, bamboo, bio-composite, oriented strand board, pre-treatment